Brain age prediction using the graph neural network based on resting-state functional MRI in Alzheimer's disease - Gao, Jingjing; Liu, Jiaxin; Xu, Yuhang; Peng, Dawei; Wang, Zhengning (Frontiers in Neuroscience, 2023)
Alzheimer's disease (AD) is a neurodegenerative disease that significantly impacts the quality of life of patients and their families. Neuroimaging-driven brain age prediction has been proposed as a potential biomarker to detect mental disorders such as AD, aiding in studying its effects on functional brain networks. Previous studies have shown that individuals with AD display impaired resting-state functional connections. However, most studies on brain age prediction have used structural magnetic resonance imaging (MRI), with limited studies based on resting-state functional MRI (rs-fMRI). In this study, we applied a graph neural network (GNN) model on normal controls to predict brain ages using rs-fMRI to patients with AD. We compared the performance of the GNN model with traditional machine learning models. Finally, the post-hoc model was also used to identify the critical brain regions in AD. The experimental results demonstrate that our GNN model can predict brain ages of normal controls using rs-fMRI data from the ADNI database. Moreover, the differences between brain ages and chronological ages were more significant in AD patients than in normal controls. Our results also suggest that AD is associated with accelerated brain aging and that the GNN model based on resting-state functional connectivity is an effective tool for predicting brain age. Our study provides evidence that rs-fMRI is a promising modality for brain age prediction in AD research, and the GNN model proves to be effective in predicting brain age. Furthermore, the effects of the hippocampus, parahippocampal gyrus, and amygdala on brain age prediction are verified.